Depression, anxiety and stress among postgraduate students in Faculty of Education of a public university in Malaysia - S., Vasugi; Che Hassan, Norlizah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Psychological problems like anxiety, depression and stress significantly exacerbate the pressure on students to perform better. These factors collectively hamper their performance leading to low academic achievement especially among postgraduate students who majority of them are working and married. This study aims to identify the level of depression, anxiety and stress among postgraduate students, and to investigate the correlation between depression, anxiety and stress based on gender, marital status and age. Methods: The study was a quantitative survey and correlational research design using a clustered random sampling, selected from all postgraduate students (179) in Faculty of Education. The DASS-21 was used as measuring tools for depression, anxiety and stress among post-graduate students. Results: Findings of the study revealed that majority of the respondents are having moderate level of depression, anxiety and stress. Meanwhile, there were strong correlations between depression, anxiety and stress. However, there were no significant differences for level of depression, anxiety and stress based on demographic factors (gender, marital status and age). Conclusion: Based on the findings, it can be concluded that depression, anxiety and stress are strongly correlated. This study can give some insight to the educators, universities administration as well as students’ family to develop common intervention on how to curb depression, anxiety and stress among postgraduate students.